AQUEUS EXTRACT OF CYPERUS ROTUNDUS RHIZOME PROTECTS AGAINST MERCURY (II) INDUCED OXIDATIVE AND RENAL STRESS IN RATS. - AHLEM BAHI; YOUCEF NECIB (International Journal of Pharma and Bio Sciences, 2015)
The study was designed to investigate the possible protective role of aqueous extract of Cyperus Rotundus in mercuric chloride induced renal stress, by using biochemical approaches. The effects of aqueous extract of Cyperus Rotundus on mercuric chloride induced oxidative and renal stress was evaluated by serum creatinine, urea and uric acid levels, kidney tissue lipid peroxidation, GSH levels, GSH-Px and GST activities. Administration of mercuric chloride induced significant increase in serum: creatinine, urea and uric acid concentration showing renal stress. Mercuric chloride also induced oxidative stress, as indicate by decreased kidney tissue of GSH level, GSH-Px and GST activities along with increase the level of lipid peroxidation. Furthermore, treatment with mercuric chloride caused a marked elevation of kidney weight and decreased body weight. aqueous extract of Cyperus Rotundus treatment markedly reduced elevated serum: creatinine, urea and uric acid levels and counteracted the deterious effects of mercuric chloride on oxidative stress markers changes caused by HgCl2 in kidney.Our results indicate that aqueous extract of Cyperus Rotundus could have a beneficial role against mercuric chloride induced nephrotoxicity and oxidative stress in rat.